Safe Firefighting Distances Using FDS and ALOHA for Oil Tank Fires - Ming-Chuan Hung; Ching-Yuan Lin; Gary Li-Kai Hsiao (Fire)
Ensuring firefighter safety during oil tank fires is paramount, given the substantial risks posed by thermal radiation. This study employs both the Fire Dynamics Simulator (FDS) and Areal Locations of Hazardous Atmospheres (ALOHA) software to simulate a severe oil tank fire scenario at the Zhushan Branch Power Plant, where two heavy oil tanks and multiple light oil tanks are located. The simulation framework divides the combustion scenario into 22.4 million grids with a grid size of 0.5 m, allowing a fine-resolution assessment of thermal radiation. Assuming a worst-case scenario involving n-Heptane combustion, the FDS simulation calculates essential parameters, including temperature, velocity, and soot distribution fields, and suggests a minimum safe firefighting distance of 22 m (equivalent to one tank diameter, 1D) for those equipped with personal protective equipment when exposed to a 5 kW/m2 heat flux. Meanwhile, ALOHA modeling extends the safety assessment, recommending a downwind safety distance of 62 m (approximately 2D) to establish a preliminary exclusion zone, crucial in early emergency response when data may be incomplete. Additionally, a grid sensitivity analysis was conducted to validate the accuracy of the numerical results. This study underscores the importance of coupling FDS and ALOHA outputs to develop a balanced, adaptive approach to firefighter safety, optimizing response protocols for high-risk environments. The results provide essential guidance for establishing safety zones, advancing standards within fire protection and emergency response, and supporting strategy development for large-scale oil and petrochemical storage facilities.